Novel immunization strategies against protozoan parasites. Proceedings of a workshop - McKeever, Declan J. (International Laboratory for Research on Animal Diseases, 1995)
The main aim of this meeting was to review those developments in the fields of immunology and immunoparasitology that have relevance to the development of vaccination strategies for ECF and trypanosomiasis. Of relevance to the control of ECF were recent developments in the elucidation of events that surround the induction of cytotoxic T lymphocytes, and the role of cytokines in the control and pathogenesis of parasitic infections. Chief areas of interest to the trypanosomiasis programme were disease-related perturbations of the immune system, the role of individual T cell subsets in immunity to parasites and the involvement of cytokines in the control and pathogenesis of parasitic diseases. More specific discussions focused on the role of CTL in parasitic infections; antigen processing for class I MHC - restricted responses; novel technologies for identifying antigens that provoke CTL responses; the role of detrimental immune responses in pathogenesis; the role of T cell subsets and their products in the control of parasitic diseases; and immunization strategies for driving immune responses towards favourable rather than detrimental mechanisms.